Validity of Student Worksheet Based on Scientific Literacy to Train Argumentation Skills on Buffer Solution - Maya Kumalasari; Suyono Suyono (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The purpose of this research is to produce student worksheet based on scientific literacy to train argumentation skills on buffer solution seen from content and construct validation. The research subject were high school students grade XI. This research is development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which is limited to the development stage to find out the validation of student worksheet. The instrument used to obtain validity data (content and construct) is a validation sheet. The validity of the developed student worksheet is based on the assessment of three validators through expert judgment namely two chemistry lecturers and one chemistry teacher. Student worksheet based on scientific literay is declared the validity criteria if it gets a minimum assessment mode of 4 (valid) from a range of 1 to 5 on a Likert scale. The results showed that all components of the assessment both content validity (relevance) and construct validity (consistency) received an assessment mode of 4 with a valid category. So that the student worksheet based on scientific literacy was declared valid to train argumentation skills on buffer solution.